Autonomous observations of biogenic N2 in the Eastern Tropical North Pacific using profiling floats equipped with gas tension devices - McNeil, Craig L.; D’Asaro, Eric A.; Altabet, Mark A.; Hamme, Roberta C.; Garcia-Robledo, Emilio (Frontiers in Marine Science, 2023)
Oxygen Deficient Zones (ODZs) of the world’s oceans represent a relatively small fraction of the ocean by volume (<0.05% for suboxic and<5% for hypoxic) yet are receiving increased attention by experimentalists and modelers due to their importance in ocean nutrient cycling and predicted susceptibility to expansion and/or contraction forced by global warming. Conventional methods to study these biogeochemically important regions of the ocean have relied on well-developed but still relatively high cost and labor-intensive shipboard methods that include mass-spectrometric analysis of nitrogen-to-argon ratios (N2/Ar) and nutrient stoichiometry (relative abundance of nitrate, nitrite, and phosphate). Experimental studies of denitrification rates and processes typically involve either in-situ or in-vitro incubations using isotopically labeled nutrients. Over the last several years we have been developing a Gas Tension Device (GTD) to study ODZ denitrification including deployment in the largest ODZ, the Eastern Tropical North Pacific (ETNP). The GTD measures total dissolved gas pressure from which dissolved N2 concentration is calculated. Data from two cruises passing through the core of the ETNP near 17 °N in late 2020 and 2021 are presented, with additional comparisons at 12 °N for GTDs mounted on a rosette/CTD as well as modified profiling Argo-style floats. Gas tension was measured on the float with an accuracy of< 0.1% and relatively low precision (< 0.12%) when shallow (P< 200 dbar) and high precision (< 0.03%) when deep (P > 300 dbar). We discriminate biologically produced N2 (ie., denitrification) from N2 in excess of saturation due to physical processes (e.g., mixing) using a new tracer – ‘preformed excess-N2’. We used inert dissolved argon (Ar) to help test the assumption that preformed excess-N2 is indeed conservative. We used the shipboard measurements to quantify preformed excess-N2 by cross-calibrating the gas tension method to the nutrient-deficit method. At 17 °N preformed excess-N2 decreased from approximately 28 to 12 µmol/kg over σ0 = 24–27 kg/m3 with a resulting precision of ±1 µmol N2/kg; at 12 °N values were similar except in the potential density range of 25.7< σ0< 26.3 where they were lower by 1 µmol N2/kg due likely to being composed of different source waters. We then applied these results to gas tension and O2 (< 3 µmol O2/kg) profiles measured by the nearby float to obtain the first autonomous biogenic N2 profile in the open ocean with an RMSE of ± 0.78 µM N2, or ± 19%. We also assessed the potential of the method to measure denitrification rates directly from the accumulation of biogenic N2 during the float drifts between profiling. The results suggest biogenic N2 rates of ±20 nM N2/day could be detected over >16 days (positive rates would indicate denitrification processes whereas negative rates would indicate predominantly dilution by mixing). These new observations demonstrate the potential of the gas tension method to determine biogenic N2 accurately and precisely in future studies of ODZs.